An Analytical Study of Gross Domestic Product Per Capita in United States Dollar for Selected Asian Countries - Majee, Mohammed Tareq; Dawod, Salam Abas; Abbas, Mustafa Hasan (Journal of Asian Multicultural Research for Social Sciences Study, 2022)
The world is divided into various countries. These countries have their own policy for economic development. There are various methods for determining economic development out of that one method or one measure is Gross Domestic Product (GDP). Every country has their own GDP which measure the performance of economy. For this study gross domestic product per capita in United States dollar has been analyzed with selected Asian countries based on respective nation’s population as on 2021. The study period is considered from 2015 to 2021. For identify difference among per capita GDP of selected nations one way ANOVA tool has been used as statistical parameter. The major finding of the study indicated as China saw increasing trend of per capital GDP for selected time period. India indicated fluctuating trend of per capita GDP for the study period. Out of selected countries Pakistan indicated lowest per capital GDP from selected countries. On an average performance of Indonesia, Philippines and Vietnam in concern with per capita GDP was same during the study period. Japan indicated highest per capital GDP out of selected countries.